Doping induced performance enhancement in inverted small molecule organic photodiodes operating below 1V reverse bias: towards compatibility with CMOS for imaging applications - Shekhar, Himanshu; Lami, Vincent; Vaynzof, Yana (Organic electronics, 2019)
Organic photodiodes (OPDs) offer a myriad of advantages over conventional inorganic photodetectors, making them particularly attractive for imaging application. One of the key challenges preventing their utilization is the need for their integration into the standard CMOS processing. Herein, we report a CMOS-compatible top-illuminated inverted small molecule bi-layer OPD with extremely low dark leakage current. The device utilizes a titanium nitride (TiN) bottom electrode modified by a [6,6]-phenyl C61 butyric acid methyl ester (PCBM) cathode buffer layer (CBL). We systemetically show that doping the CBL enhances device's low voltage (below 1V reverse bias) photoresponse by increasing the linear dynamic range (LDR) and making the bandwidth of the photodidoe broader without compromising the leakage current. The optimized device exhibits a dark leakage current of only ∼6×10−10 A/cm2 at −0.5V. The external quantum efficiency (EQE) at 500nm reaches 23% with a calculated specific detectivity as high as 7.15×1012cmHz1/2/W (Jones). Also the LDR approaches 140dB and the bandwidth is about 400kHz, at −0.5V bias. The proposed device structure is fully compatible with CMOS processing and can be integrated onto a CMOS readout circuit offering the potential to be applied in high-performance large-scale imaging arrays.
Gesehen am 07.08.2019